An ion-sieve-tailored biomimetic porous nanofiber as an efficient adsorbent for extraction of lithium from brine. (13th February 2023) - Li, Xiulei; Wang, Zhihui; Zhang, Hexin; Zhang, Wen; Jiang, Jiacun; Guo, Ruili
Abstract : Schematic illustration of the synthesis of biomimetic porous nanofibrous H1.6 Mn1.6 O4 and a possible mechanism for the high-efficiency and rapid selective extraction of Li + from brine. Abstract : A lithium-ion sieve (H1.6 Mn1.6 O4 ) with a porous nanofiber structure imitating the loofah skeleton was prepared in the currently reported work by performing electrospinning and high-temperature calcination. This prepared NFs@LIS-6:6 showed a controllable porous nanofiber structure and abundant Li + adsorption sites. The separation coefficient for Mg 2+ reached 421.68. Surprisingly, compared with particulate adsorbents, NFs@LIS-6:6 showed a 94.44% higher Li + adsorption rate and 33.90% higher adsorption capacity, indicating an extraordinary potential for extracting Li + from salt lake brine.